Identification of Land Acquisition Planning Documents for the Proposed Religious Tourism Parking Lot at the Ki Ageng Pandanaran Mausoleum in Semarang City - Andreas Rudiyanto; Sri Wahyuni; Eko Sugiarto; Firda Diartika (Asian Journal of Philosophy and Religion, 2026)
The research methodology uses a descriptive qualitative approach through regulatory analysis, inventory of existing conditions, and conformity assessment with the Semarang City Regional Spatial Plan. The results of the study show that the existing parking conditions in the cemetery area are not able to accommodate the increasing number of vehicles. The required land area is around 1,139 m² with the status of land owned by residents, so a fair land procurement mechanism is needed and in accordance with the rules. This study recommends the preparation of a Feasibility Study, Detailed Engineering Design, and environmental analysis as the basis for development implementation. Thus, the preparation of the DPPT is expected to provide legal certainty, protection for affected communities, and support the sustainable development of religious tourism destinations.